Response to the Vegetative Growth of Arabica Coffee Plants (Coffea Arabika) Due to Seed Depth Test and Application of Eco Enzyme - Yudi Siswanto; Isnar Sumartono; Muhammad Wasito; Nurloza Khatimah (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The purpose of this study was to determine the vegetative growth response of Arabica coffee (Coffea arabica) resulting from different seed planting depths and eco-enzyme application, as well as their interaction effects. The research was conducted in Sei Sikambing B Village, Medan Sunggal District, Medan City, North Sumatra Province, at an altitude of approximately ±25 meters above sea level. The study took place from July to October 2025. This research used a Factorial Randomized Block Design (RBD). The first factor was seed depth, denoted as "K," consisting of K0 = 0 cm, K1 = 0.5 cm, K2 = 1.0 cm, and K3 = 1.5 cm. The second factor was eco-enzyme application, denoted as "E," consisting of E0 = 0 ml/liter of water, E1 = 100 ml/liter of water, E2 = 200 ml/liter of water, and E3 = 300 ml/liter of water. The observed parameters included germination percentage (%), germination time (days), plant height (cm), number of leaves (leaves), and stem diameter (mm). The results showed that seed depth and eco-enzyme application significantly affected several parameters, including germination percentage, germination time, plant height, number of leaves, and stem diameter. However, the interaction between seed depth and eco-enzyme application did not have a significant effect on germination percentage, germination time, plant height, number of leaves, or stem diameter.